2021
DOI: 10.18295/squmj.2021.21.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Light Microscopic Features of the Oral Mucosa in Predicting Post-mortem Interval

Abstract: Objectives: The post-mortem interval (PMI) refers to the amount of time elapsed between death and discovery of the body. This study aimed to evaluate light microscopic cellular changes in the oral mucosa and identify the potential of this method for predicting PMI. Methods: This prospective study was conducted between July 2016 and January 2018 at the Institute of Dental Sciences, Siksha ‘O’ Anusandhan University, Bhubaneswar, India. A total of 150 post-mortem (including 75 gingival and 75 buccal mucosa sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 17 publications
2
8
0
1
Order By: Relevance
“…The time intervals since death were < 12.5, 12.5–20.5, and > 20.5 h. The authors examined epithelial changes, connective tissue, and degeneration in the buccal area. ( Patro et al, 2021 ) Histological changes such as homogenisation, cytoplasmic vacuolisation, nuclear shrinkage, and chromatin clumping in cells were observed in tissues at < 12.5 h. Similar findings were detected at intervals of 12.5–20.5 and > 20.5 h, although to a greater extent. Degeneration of the acinar mucosa occurred at intervals of 12.5–20.5 and > 20.5 h.( Patro et al, 2021 ).…”
Section: Literature Reviewsupporting
confidence: 61%
See 2 more Smart Citations
“…The time intervals since death were < 12.5, 12.5–20.5, and > 20.5 h. The authors examined epithelial changes, connective tissue, and degeneration in the buccal area. ( Patro et al, 2021 ) Histological changes such as homogenisation, cytoplasmic vacuolisation, nuclear shrinkage, and chromatin clumping in cells were observed in tissues at < 12.5 h. Similar findings were detected at intervals of 12.5–20.5 and > 20.5 h, although to a greater extent. Degeneration of the acinar mucosa occurred at intervals of 12.5–20.5 and > 20.5 h.( Patro et al, 2021 ).…”
Section: Literature Reviewsupporting
confidence: 61%
“…Epithelial surface cell evaluation involves the examination of vacuolisation, cell outline, homogeneity, nuclear outline, nuclear vacuolisation, chromatin clumping, karyorrhexis, pyknosis, karyolysis, epithelial cell separation, antibody-antigen interaction, and loss of tissue architecture. ( Muthukrishnan et al, 2018 , Patro et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Light microscopy images are also widely used to identify post-mortem intervals, which collectively refer to the phenomena appearing after the death of an animal. Patro et al [62] observed cellular changes in light microscopy images of oral tissues during the postmortem interval. They analyzed the ecological changes in various oral tissues; however, the importance of acquiring more precise and stable images in observing the connective tissue was mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…Kerge et al, 2018;Temple et al, 2014), cukura diabēta gadījumā(Seifi et al, 2014;Jajarm et al, 2008) vai saistībā ar pēcnāves izmaiņām mutes dobuma audos(Patro et al, 2021). Sejas šķeltņu audu saistība ar iekaisuma procesu ir iepriekš aprakstīta citos pētījumos(Seidel et al, 2022).…”
unclassified